2012
DOI: 10.5812/hepatmon.6064
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL28B SNP With Progression of Egyptian HCV Genotype 4 Patients to End Stage Liver Disease

Abstract: Background: IL28B single nucleotide polymorphisms (SNPs) play important roles in the management of hepatitis C virus (HCV) infections and are strongly associated with spontaneous and treatment-induced HCV clearance. Objectives: In the present study, the association between IL28B variants and the progression of HCV infection in Egyptian patients infected with type 4a virus will be examined. Patients and Methods: Frequencies of the protective genotype C/C of SNP, rs12979860 were determined in healthy subjects, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 27 publications
5
11
2
Order By: Relevance
“…The results of this study revealed IL28B rs12979860 C T genotype as the commonest genotype (68.9 ) and is in agreement with previous studies done on Egyptian patients (19,(30)(31)(32), suggesting a possible role of this genotype in the transition of a normal hepatocyte into an abnormal one. This genotype distribution was suggested to be a consequence of environmental or ethnic variation (30,32).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The results of this study revealed IL28B rs12979860 C T genotype as the commonest genotype (68.9 ) and is in agreement with previous studies done on Egyptian patients (19,(30)(31)(32), suggesting a possible role of this genotype in the transition of a normal hepatocyte into an abnormal one. This genotype distribution was suggested to be a consequence of environmental or ethnic variation (30,32).…”
Section: Discussionsupporting
confidence: 81%
“…The frequency of CC genotype in our samples was smaller than all those mentioned above. This may be explained by the results obtained by El-Awady et al that showed a sharp decline in the C C genotype along the progression of chronic HCV infection towards the end-stage liver disease (31), and the majority of our patients had advanced fibrosis stages (F3-F4) When applying our REPTree, IL28B genotype was chosen as the most decisive variable, occupying the root node, to predict advanced fibrosis stages. IL28B gene plays a role in the outcome of chronic hepatitis C (30).…”
Section: Discussionmentioning
confidence: 94%
“…One of these SNPs is rs12979860 C/T, it is pivotal in predicting the outcome of HCV infections (Thomas et al, 2009). In El-Awady et al (2012), it was demonestrated that genotype C/C is significantly associated with viral clearance during the acute stage of HCV infection. The sharp decline in the C/C genotype from healthy to CHC subjects and the total absence of the C/C genotype in end stage liver disease, which were reported in this study, indicated a pivotal role of this genotype against disease progression in HCV infected patients.…”
Section: Il28b Rs12979860 Gene Polymorphism In Egyptianmentioning
confidence: 99%
“…After our selection, 7 casecontrol studies including 1152 HCC and/or LC cases and 1326 controls fulfilled the inclusion criteria (Barreiro et al, 2011;Fabris et al, 2011;Falleti et al, 2011;Agundez et al, 2012;El-Awady et al, 2012;Eurich et al, 2012;Ren et al, 2012). The quality of the studies was considered acceptable for our meta-analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…There were 5 case-control studies Agundez et al, 2012;El-Awady et al, 2012;Eurich et al, 2012;Ren et al, 2012), which had been performed to study the rs12979860 poly morphism and HCC risk. The results of the meta-analysis are shown in Table 3.…”
Section: Evaluation Of the Il-28b Rs12979860 Polymorphism And Associamentioning
confidence: 99%